Construction of core-shell BaFe12O19@MnO2 composite for effectively enhancing microwave absorption performance. Issue 12 (15th June 2021) - Hu, Fanfan; Nan, Hu; Wang, Mengqi; Lin, Ying; Yang, Haibo; Qiu, Yun; Wen, Bo
Abstract: BaFe12 O19, a traditional ferrite, has always been extensively investigated as a microwave absorption material because of the application value. Herein, the core-shell BaFe12 O19 @MnO2 composite was designed and constructed successfully by a facile hydrothermal method. By introducing nanostructured MnO2, a typical dielectric loss medium, the electromagnetic wave absorption performance is effectively enhanced. The core-shell structure contributes to high interface polarization, thereby promoting the attenuation of electromagnetic waves. In addition, the optimal temperature of the hydrothermal reaction was explored through the characterization of the morphology and the analysis of microwave absorption performance. The result exhibits that the maximum reflection loss of the prepared BaFe12 O19 @MnO2 -170 reaches -54.39 dB and the effective absorbing bandwidth reaches 4.64 GHz. The simple preparation method and attractive performance make BaFe12 O19 @MnO2 a promising candidate as microwave absorbers.